Evolution of volatile compounds in 'Cuoredolce®' and 'Rugby' mini‐ watermelons (Citrullus lanatus (Thunb.) Matsumura and Nakai) in relation to ripening at harvest. (5th December 2019) - Bianchi, Giulia; Provenzi, Lia; Rizzolo, Anna
Abstract: BACKGROUND: Watermelon is appreciated for its nutritional properties and for its flavor. Among the flavor‐active compounds that it contains, volatiles play a key role being responsible for aroma. Recent breeding activity has led to the release of mini‐watermelons with reduced fruit weight. This paper reports on the characterization of aroma profiles of 'Rugby' and 'Cuoredolce®' novel mini‐watermelon cultivars at the ripening stage. The main volatiles were identified and quantified using headspace solid‐phase microextraction gas‐chromatography mass spectrometry (HS‐SPME‐GC–MS), and their concentrations were correlated with the E‐nose profile. The potential contribution of volatile compounds to the fruit aroma was evaluated by computing the odor activity values (OAV). RESULTS: Twenty main volatile compounds were identified: aldehydes (9), alcohols (4), ketones (2), and terpenes and terpenoids (5). C‐9 aldehydes and alcohols were the prevalent compounds. The two cultivars differed in precocity, with 'Rugby' being riper from the early stage considered. Many apocarotenoids with desirable olfactory notes were detected in the volatile profile of 'Rugby'. Four e‐nose sensors' signals significantly changed with variety and ripening stage: W1W and W2W were positively correlated and W6S was negatively correlated with all identified volatiles, while W3S showed a negative correlation with 6‐methyl‐5‐hepten‐2‐one, the major lycopene catabolite. CONCLUSIONS: The aroma profiles described here contribute to the characterization of 'Cuoredolce®' and 'Rugby' mini‐watermelon cultivars. Electronic‐nose measurement was able to discriminate between cultivars and, to a lesser extent, among ripening stages. © 2019 Society of Chemical Industry